Recent Advances in the Chemistry of Heavier Group 14 Enolates. Issue 67 (19th September 2019) - Haas, Michael
Abstract: Recently heavier Group 14 enolates showed their importance and applicability in a broad range of chemical transformations. They were found to be key intermediates during the synthesis of photoinitiators, as well as during the formation of complex silicon frameworks. This Minireview presents general strategies towards the synthesis of heavier Group 14 enolates (HG 14 enolates). Structural properties, as well as their spectroscopic behavior are outlined. This study may aid future development in this research area. Abstract : Heavy duty : This minireview presents a summary of synthetic protocols towards the formation of heavier metal enolates. Furthermore, the spectroscopic behavior and the structural data for HG 14 enolates were summarized. In addition, it outlines the recent advances in this research field.